Kaempferol promotes apoptosis and inhibits proliferation and migration by suppressing HIF-1α/VEGF and Wnt/β-catenin activation under hypoxic condition in colon cancer - Muhammad Haroon; Sun Chul Kang (Applied Biological Chemistry)
Abstract A naturally occurring flavonoid compound found in several fruits and vegetables, kaempferol has garnered interest for its potential anticancer effects. The present investigation illustrates that kaempferol has multi-faceted anti-tumor effects in hypoxic colon cancer cells, HCT-15 (ATCC) and HCT-116 (KCLB) by inhibiting HIF-1α/VEGF angiogenesis, Wnt/β-catenin signaling, and epithelial-mesenchymal transition (EMT) progression. In conditions of hypoxia, kaempferol inhibited the stabilization of HIF-1α and its downstream targets (VEGF, ANG1, VEGFR2), while also obstructing Wnt/β-catenin activation by decreasing β-catenin and modifying the expression of pathway components (c-Myc, Cyclin-D1, LEF1, APC, and Axin-2). Kaempferol mitigated hypoxia-induced EMT by reinstating E-cadherin and inhibiting N-cadherin, Vimentin, and MMP-2/9, which corresponded with diminished migration in transwell and wound-healing assay. Mechanistic investigations demonstrated dual regulation of HIF-1α transcriptional activity (HRE luciferase) and MAPK signaling (p-ERK/p-38), in conjunction with ROS-induced DNA damage and intrinsic apoptosis (cleaved caspase-3/9 and Bcl-2 protein expression). The impact on angiogenesis, EMT, and survival pathways significantly diminished the proliferation, invasion, and metastatic capacity of hypoxic colon cancer cells which identifies kaempferol as an innovative multi-pathway inhibitor, thereby offering a strong justification for its advancement as a therapeutic agent for advanced colorectal cancer. Graphical abstract